Analisis Penilaian Kinerja Karyawan terhadap Motivasi Kerja pada Perusahaan - Sharleen Aulia Redian; Huriyana Inas Sumaryan; Kriara Latifah Dinar; Tias Wahyuni; Sri Sundari; Marisi Pakpahan (Jurnal Syntax Admiration, 2024)
The purpose of this study is to analyze the importance of employee performance appraisal on work motivation in the company with a qualitative approach. This research method uses analysis of documents, articles, and journals related to employee performance appraisal of work motivation. This research is a research using the literature study method or literature review, through a qualitative approach, it is hoped that the research can provide deep insight into the Analysis of Employee Performance Appraisal on Work Motivation in the Company. employee and company development. Motivation is also a key factor in maintaining high performance, with companies using various motivational models to direct and control employees according to company goals effectively and efficiently. Thus, performance appraisal and work motivation become important elements in improving company performance and achieving the desired goals.